PENGENDALIAN LALU LINTAS JALAN BERBAYAR ELEKTRONIK: STUDI PERATURAN GUBERNUR DKI JAKARTA NO. 149 TAHUN 2016 - Mustakim Mustakim (Universitas Nasional, 2020)
Congestion in the capital city of Indonesia, Jakarta, is getting worse and acute. The data of Metro Jaya Police Department shows that the addition number of new cars reaches 250 units per day on average while motorcycle reaches 1.250 units per day. The total number of vehicles until the end of year 2014 di Jakarta is 17.523.967 units dominated by two wheeled vehicles which is up to 13.084.372 units. It was followed by car, 3.226.009 units, goods carrier car 673.661 units, bus 362.066 units, and specific purpose car 137.859 units. Therefore, in order to overcome those problems, Jakarta, the capital city of Indonesia, applied Electronic Road Pricing (ERP) aiming to charge vehicles passing through certain road in certain specific time. The character of this study is normative with constitutional approach and a study of Jakarta Governor Regulation No. 149 Year 2016. The result showed that the substance of Jakarta Governor Regulation No. 149 Year 2016 about electronic road pricing traffic control was qualified as against the principle of act and regulation formation as what has been regulated by act No. 12 Year 2011 especially related to the kind of charging, the amount of the charge, and the penalty of the violation toward the ERP. The legal steps by changing to adapt related regulation about the amount of the charge and the penalty refers to constitution and / or conducting the trial to the Supreme Court to judge the regulation.